ETHICS IN THE CONTEXT OF ORGANIZATIONS (Fiep Bulletin - online, 2011)
Ethics strengthens the proper conduct and ways to promote it, according to the prevailing concepts in society or in specific social groups. Clear example is the code of ethics of advertising, which condemns the comparisons between products, brands or companies, as well as false advertising. Advertising agencies will arrange to monitor compliance with these and other rules of conduct, through a council ofself-regulation. For fans of the ethic of conviction, who contravenes the guidelines established to assumethe burden of transgression, suffering their penalties and bear the burden of guilt and remorse. On the other hand, who, doing their duty can only refer to God as the result of the action. So significantly ifferent fans of the ethics of responsibility following two steps: first reflect on the facts and present conditions then deliberate. Literature searches were carried out in books.
Keywords: ethics; organization; client